Managing donors and donation sessions to improve donor service and session productivity. (29th January 2016) - Nyberg‐Oksanen, E.; Morgan, S.; Sydenham, V.; Georgsen, J.; Jansen, E.; ,
Abstract : Background and Objectives: The European Blood Alliance's Benchmarking group (EBA BMG) has facilitated three collection productivity workshops (2008–15). Productivity improvements are evident in some European blood services, but fewer than anticipated. European blood services sometimes lack data, experience and state of the art technology to implement opportunities to improve productivity. With the decline in red cell demand across the developed world alongside constrained healthcare budgets and the changing expectations of the evolving donor base, as countries see a need to recruit younger donors, the challenge is balancing increasing donor expectations with higher productivity targets. Materials and Methods: Against each identified key element, we have collected key performance indicators (KPIs) and benchmarked them across European blood services. We have also identified technologies, which we call enablers that could help blood services improve performance. Results: The analysis performed by the EBA BMG identifies the key elements associated with efficient management of donors and donation sessions. Conclusions: With these best practices and KPIs, it is possible for blood services to increase session productivity and donor satisfaction through low deferrals, low end‐to‐end donation time and smooth, consistent, yet 'tailored' individual service inside the session.